PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS IV SD NEGERI 166 PEKANBARU - Rasmi, Widya; Witri, Gustimal; Kurniaman, Otang (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research is motivated by the facts found in the class IV SDN 166 Pekanbaru, which shows the results of learning mathematics is still relatively low. Formulation of the problem in this research is: